Letter or Sermon? The Analysis of Augustine’s "De Bono Viduitatis" - Katreničová, Anabela (Vox Patrum, 2023)
St. Augustine’s work De bono viduitatis written in 414 is not a treatise but a letter addressed to widow issued from a noble Roman family named Juliana. She with her daughter and mother-in-law attempts to live the consecrated way of life. Under the strong influence of the ascetism and moralism of Pelagius, she begs Augustine to acquire the essential instructions for their devotion. Augustine in his answer proposes the original teaching on the widowhood based on the Holy Scripture, especially on the letters of apostle Paul, and encourages the women in their consecration to observe the goods of the widowhood. Nevertheless, St. Augustine does not write this letter only to Juliana. He desires that this letter will be spread to the other widows as well. The aim of our paper is to analyse the Augustine’s letter to Juliana and focus our interest on the homiletical forms used by St. Augustine. Our argumentation is based on the analyse of this letter and on its comparison with Augustine’s style of preaching. Examining the rhetoric elements used and known by St. Augustine as they are summarized in the Book Four of his treatise On Christian Doctrine it enables us to present the style of Augustine – preacher and consequently to find some similarity and differences.